PERAN EKONOMI BERBASIS KOMUNITAS DALAM MEMBERDAYAKAN MASYARAKAT PERSPEKTIF MAQASHID SYARIAH: Studi Pada UKMP Depok - Tasya Hadi Syahputri (2022)
The economic development of the city of Depok over the last ten years is still relatively stagnant. This is reflected in the macroeconomic data this city over the past decade which shows uneven progress. If the current condition continues, the city of Depok's economic development target, as mentioned in the RPJPD 2006-2025, will be hampered. Therefore, economic development activities based on empowerment are required so that the community can participate actively. The purpose of this research is to look into the role of the community-based economy in empowering the UKMP community. This research used a descriptive qualitative technique and is based on a case study. Primary and secondary data were used in this research. According to the findings of the research, the community-based economic model used in the UKMP community is a reflection of the three fields of activity in this community, namely marketing, education, and social services. Then, social relationships as the foundation of a community-based economy are well developed in this community. Empowerment is analyzed using five indicators derived from maqashid sharia. The results show that the UKMP community has played a good role in empowering its members.